Dark parts of the universe - Miller, Samuel, 1991- (Katherine Tegen Books, an imprint of HaperCollinsPublishers, 2024)
In the all-white Missouri town of "Calico Springs, Willie's life has been defined by two powerful forces: God and the river. The 'miracle boy' died for five minutes as a young child, and ever since, Willie is certain he survived for a reason, but that purpose didn't become clear until he found the Game. The Game is called Manifest Atlas, and the concept is simple: enter an intention and the Game provides a target--a blinking blue dot on the map. Willie's second time playing Manifest Atlas, his intention takes him to an ominous target: three empty graves. Willie is sure the Game is telling him he's going to die. Willie's older brother Bones doesn't believe him, but their friends are intrigued. Sarai, a girl from across the river, sets the next intention: something bloody. The group follows the Game's coordinates and they discover something even more unsettling than the graves: a dead body. Sarai's stepfather's body. The Game is suddenly personal"--